Effects of endogenous proteins on rice digestion during small intestine (in vitro) digestion. (15th May 2021) - Li, Changfeng; Cao, Panpan; Wu, Peng; Yu, Wenwen; Gilbert, Robert G; Li, Enpeng
Highlights: The physical barrier caused by protein influences starch digestion in cooked rice. Protein/starch hydrogen-bonding interactions are significant in uncooked rice. The type of protein has negligible effect on in vitro rice starch digestion. Abstract: Rices with higher protein contents are nutritionally desirable. This study investigates the effects of endosperm proteins on starch in vitro digestibility in cooked and uncooked rice, and the mechanisms underlying any changes. The composition of rice endosperm proteins and the morphologies of proteins and starch granules were determined by SDS-PAGE and confocal microscopy. Starch molecular fine structure was examined using size-exclusion chromatography. In vitro digestion showed that the digestion rate coefficients ( k ) of cooked rice flour were significantly lower than those of isolated starch or of a starch-protein mixture. (e.g for samples from SWR4, k is 9.6, 12.9 and 11.6 × 10 -2 min −1 for cooked rice flour, isolated starch and starch-protein mixture, respectively). For uncooked samples, digestion rate coefficients were 1.4, 1.5 and 1.8 × 10 -2 min −1 for flour, starch-protein mixture and starch, respectively. The digestion rates in cooked samples were higher than those in uncooked samples. This suggests that, in cooked samples, starch digestion rates are more affected by the protein physical barrier than by some chemical effect (e.g. hydrogen bonding between protein and starch), while in uncooked samples, a chemical effect from protein is more pronounced than a physical barrier from protein.